Artificial Intelligence in Prosthodontics - Schwendicke, Falk; Mohammad Rahimi, Hossein; Tichy, Antonin (Dental clinics of North America, 2025)
Artificial intelligence (AI) has significantly impacted numerous industries, including health care, dentistry, and specifically prosthodontics. This review focuses on AI's role in prosthodontics, detailing its use in diagnosis, design, and manufacturing. AI-driven systems analyze intraoral scans, improve prosthetic planning, and aid in robotic procedures. Emerging technologies, such as generative AI for prosthetic design and AI-driven material innovation, are discussed alongside the ethical and regulatory challenges facing broader adoption. The review highlights AI's potential to transform prosthodontic workflows, facilitating more accurate, efficient, and personalized care, while also pointing to future developments such as real-time monitoring and enhanced collaboration platforms.
Keywords: Artificial Intelligence; Dental Prosthesis Design; Prosthesis; Image analysis; Humans; zubní protéza - design; Prosthodontics; Deep learning; Intraoral scan; stomatologická protetika; robotika; Computer vision; AI; lidé; umělá inteligence; Robotics